Case Report: A rare case of intramedullary spinal cord abscess with brain abscess caused by Klebsiella pneumoniae underwent surgical intervention - Zhang, Wenjuan; Guo, Xiangyu; Xu, Xuejun; Deng, Bing (Frontiers in Surgery, 2024)
Background: Intramedullary Spinal Cord Abscess (ISCA) is an uncommon infectious disease of the central nervous system. Since its first report in 1830, there have been very few documented cases associated with it. Here, we present a case of ISCA with cerebral abscess caused by Klebsiella pneumoniae. Case presentation: A 55-year-old male patient presented with head and neck pain, fever, and left limb weakness for 5 days. The diagnosis of ISCA with brain abscess caused by Klebsiella pneumoniae was confirmed through sputum culture, cerebrospinal fluid gene test, pus culture, and magnetic resonance imaging (MRI) as well as computerized tomography (CT) scan. The patient had a history of pulmonary tuberculosis and old tuberculous foci were observed in the lung. Initially considering tuberculosis as the cause due to unclear etiology at that time, anti-tuberculosis treatment was administered. However, due to rapid deterioration in the patient's condition and severe neurological dysfunction within a short period of time after admission, surgical intervention including incision and drainage for intramedullary abscess along with removal of brain abscess was performed. Subsequent postoperative follow-up showed improvement in both symptoms and imaging findings. Conclusion: Early diagnosis of central nervous system (CNS) abscess coupled with prompt surgical intervention and administration of appropriate antibiotics are crucial factors in preventing disease progression and reducing mortality rates.